1990
DOI: 10.2135/cropsci1990.0011183x003000040035x
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Covariation in Stover Digestibility Traits in Diallel Crosses of Maize

Abstract: In the cooler regions of the world, the area under forage maize (Zea mays L.) production has increased, and breeding for digestibility has gained importance. This study was conducted on digestibility traits of stover in maize forage, to determine variation, as analyzed by the combining‐ability approach, and correlation coefficients (r) in these traits and r between these and dry matter (DM) yield traits. Diallel crosses among 12 inbred lines were evaluated at silage and grain harvests for 2 yr at two agro‐clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 0 publications
1
16
0
3
Order By: Relevance
“…Numerous works proved large genetic variations in the in-vitro digestibility of maize, either for whole plants or cell walls parts (eg, Gallais et al, 1976;Deinum and Bakker, 1981;Vattikonda and Hunter, 1982;Deinum et al, 1984;Deinum and Struik, 1985;Deinum, 1988;Dhillon et al, 1990b; Dolstra and Medema, 1990;Geiger et al, 1992;Hunt et al, 1992;Seitz et al, 1992;Dardenne et al, 1993;Dolstra et al, 1993;Wolf et al, 1993;Barrière et al, 1993a;Coors et al, 1994;Lundvall et al, 1994;Argillier et al, 1995). In early lines, according to Dolstra and Medema (1990) (Argillier et al, 1995) When considering the digestibility of whole plants, as well as stover, stalks or cell-walls, GCA effects for in-vitro values of digestibility were often preponderant over SCA effects.…”
Section: Grain Content and Grain Composition In Silage Maizementioning
confidence: 99%
“…Numerous works proved large genetic variations in the in-vitro digestibility of maize, either for whole plants or cell walls parts (eg, Gallais et al, 1976;Deinum and Bakker, 1981;Vattikonda and Hunter, 1982;Deinum et al, 1984;Deinum and Struik, 1985;Deinum, 1988;Dhillon et al, 1990b; Dolstra and Medema, 1990;Geiger et al, 1992;Hunt et al, 1992;Seitz et al, 1992;Dardenne et al, 1993;Dolstra et al, 1993;Wolf et al, 1993;Barrière et al, 1993a;Coors et al, 1994;Lundvall et al, 1994;Argillier et al, 1995). In early lines, according to Dolstra and Medema (1990) (Argillier et al, 1995) When considering the digestibility of whole plants, as well as stover, stalks or cell-walls, GCA effects for in-vitro values of digestibility were often preponderant over SCA effects.…”
Section: Grain Content and Grain Composition In Silage Maizementioning
confidence: 99%
“…The high digestibility of some brown-midrib mutants was the first indication of a great genotypic variation in the digestibility of maize plants (see review Barriere & Argillier, 1993) . Since then, genotypic variations for in vivo, in sacco, and in vitro digestibility of the dry matter (DM) or organic matter (OM) of the whole plant or of the stover part have been highlighted among normal maize hybrids (Deinum & Bakker, 1981 ;Vattikonda & Hunter, 1983 ;Deinum & Struik, 1985 ;Deinum, 1988 ;Dhillon et al ., 1990 ;Dolstra & Medema, 1990 ; Barriere et al ., 1992 ;Dardenne et al ., 1993 ;Flachowsky et al ., 1993 ;Wolf et al ., 1993) . It can be suggested that differences in forage maize feeding value are expressed best as differences in animal performance (e .g ., milk production or daily gain) .…”
Section: Introductionmentioning
confidence: 99%
“…All entries of the various trials were harvested on the same day and not separately at a more precisely determined growing stage as has been done, for example, in related research in Germany Dhillon et al ., 1990 ;Zimmer et al ., 1990 ;Gurrath, 1991) . This is allowed since in these late developmental stages stalk-dcw% is a stable trait which is not affected by either environmental or developmental variation (Dolstra & Me- However, our data show the latter to be superior owing to a higher broad-sense heritability .…”
Section: Discussionmentioning
confidence: 99%